Exploring the complex and non-linear evolution of Chinese international students' experiences in US colleges. Issue 6 (19th September 2018) - Heng, Tang T.
ABSTRACT: This article contests the narrative of Chinese international students (internationals for short) as passive and problematic to reveal the complexity and fluidity of their experiences. Simultaneously, it troubles the overly linear approach of stage theory in understanding internationals' adjustment. Following nine first- and nine second-year students in US colleges over a year and involving them in semi-structured interviews and journal prompts, this research examined how they evolved. Findings show that while participants grew on academic and personal fronts, their experiences remained multi-dimensional, with second years being less sanguine and reporting challenges different from first years. This article argues that seeing Chinese internationals' evolution as an uneven ascent affords a more nuanced understanding compared to a U-shape stage theory as it recognizes that while internationals are evolving, new situations provide challenges which they learn to overcome. Consequently, Chinese internationals' growth troubles the deficit discourse around them and departs from pre-existing research around postgraduates. Findings spell implications for how the college community should enhance transcultural understanding and how future research around internationals could develop.